Forming and coating process of high, medium and low strength aluminum-clad steel wire for optical cable accessories

By forming Cu6Sn5 nanoparticles and graphene oxide on the surface of the aluminum-clad steel wire, nanotin antimony oxide is synthesized, combined with composite gel and carbon fiber filler, the problem of thin and easy to destroy the surface of the aluminum-clad steel wire is solved, and tensile resistance, conductive performance and corrosion resistance are improved to meet the application needs of optical cable accessories.

CN118969402BActive Publication Date: 2025-02-28SHANDONG LUQIANG ELECTRICAL POLYTRON TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411136856.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-02-28
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

The thickness of the aluminum cladding layer on the surface of the aluminum-clad steel wire is thin, and the thermal physical properties of aluminum and steel are large, which leads to the easy damage of the aluminum cladding layer and the phenomenon of steel exposure, resulting in reduced corrosion resistance, low bonding strength, and uneven coating, which affects the conductivity and corrosion resistance. The tensile performance of the existing aluminum-clad steel wire is difficult to meet the application of optical cable accessories.

Method used

By forming Cu6Sn5 nanoparticles arranged in sequence on the pretreated steel wire surface of the acid etching wire, the roughness of the wire surface is increased, and during the high-temperature extrusion process, the composite filler and aluminum wire glued on the surface of the steel wire can be embedded into the formed concave-convex structure, thereby improving tensile resistance. At the same time, nanotin antimony oxide is synthesized on the surface of graphene oxide, and the composite is filled between aluminum-clad copper wires to improve the conductivity and corrosion resistance. The composite filler formed by composite gel and carbon fiber is filled between the semi-finished aluminum-clad steel wire to increase toughness and tensile strength.

Benefits of technology

The tensile and conductive properties of aluminum-clad steel wire are improved, the corrosion resistance is enhanced, the problem of easy destruction of aluminum cladding is avoided, more uniform cladding is achieved, and the overall mechanical performance and service life is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004999673420000161
    Figure BDA0004999673420000161
Patent Text Reader

Abstract

The invention discloses a forming and coating process method of high, medium and low strength aluminum-clad steel wires for optical cable accessories, and belongs to the technical field of aluminum-clad steel wire strands for optical cable accessories. The preparation method comprises the following steps: placing the modified steel wire in a wire drawing machine for drawing, washing and drying to obtain the drawn modified steel wire; gluing the aluminum wire on the surface of the drawn modified steel wire to form strands to obtain a semi-finished aluminum-clad steel wire; adding composite gel and carbon fiber to ethanol, stirring evenly to obtain a composite filler; dipping the semi-finished aluminum-clad steel wire into the composite filler, taking it out, drying it, placing it in a continuous extrusion coating machine for extrusion, and winding it after cooling and drying to obtain the initial aluminum-clad steel wire. The initial aluminum-clad steel wire is added to the composite material, stirred, taken out, and dried to obtain the finished aluminum-clad steel wire. The carbon fiber and composite gel in the composite filler interact with each other and are filled to the surface of the modified steel wire, thereby increasing the bonding strength between the aluminum wire and the copper wire, and making the coating more uniform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum-clad steel wire strands for optical cable accessories, and in particular to a forming and coating process for high, medium and low strength aluminum-clad steel wires for optical cable accessories. Background Art

[0002] Aluminum clad steel wire is made of high-strength steel as the core material and aluminum as the outer layer material through continuous extrusion and continuous coating technology. Aluminum clad steel wire combines the advantages of steel and aluminum, has strong anti-rust ability and high strength, and also has good conductivity. It can be widely used in outdoor high-voltage power transmission optical cables. Due to the many combinations of aluminum layer thickness and steel wire strength, it has great design flexibility. Aluminum clad steel wire is often used in overhead line products, including conductor reinforcement cores, ground wires, transmission lines, optical cable accessories, etc.

[0003] The aluminum coating on the surface of the aluminum clad steel wire is relatively thin, and the thermal physical properties of aluminum and steel are quite different, which makes the aluminum coating easily damaged during the production process of the aluminum clad steel wire, and the steel is easily exposed, resulting in a decrease in corrosion resistance and low bonding strength. The uneven coating causes different corrosion resistance of the aluminum clad steel wire, affecting the conductivity and corrosion resistance of the aluminum clad steel wire. The tensile properties of the existing aluminum clad steel wire are difficult to meet the application in optical cable accessories, and it is necessary to improve the tensile strength of the aluminum clad steel wire. Summary of the invention

[0004] The purpose of the present invention is to provide a forming and coating process method for high, medium and low strength aluminum clad steel wires for optical cable accessories: Cu6Sn5 nanoparticles arranged and distributed in sequence are formed on the surface of acid-etched pretreated steel wire, thereby increasing the surface roughness of the steel wire, and during the high-temperature extrusion process of the aluminum clad steel wire, the composite filler and the aluminum wire glued on the surface of the steel wire can be embedded in the formed concave-convex structure, thereby improving the tensile performance; nano-tin antimony oxide is synthesized on the surface of graphene oxide, and the two are compounded and filled between the aluminum clad copper wires, which has good conductive properties, and during the high-temperature extrusion process, the nano-tin antimony oxide falls off, and its nano size can be filled into the micro gaps of the aluminum clad copper wires, thereby improving the tensile strength; the composite filler formed by the composite gel and carbon fiber is filled between the semi-finished aluminum clad steel wires, thereby increasing the toughness and tensile strength of the aluminum clad steel wire; the carboxymethyl chitosan thio derivative and the oil tea shell extract are mixed and coated on the surface of the initial aluminum clad steel wire to form an anti-corrosion layer, thereby further enhancing the anti-corrosion performance of the aluminum clad steel wire, and are coated on the surface of the aluminum clad steel wire as an insulating layer, thereby having an insulating effect.

[0005] The technical problems to be solved by the present invention are as follows: the aluminum coating on the surface of the aluminum clad steel wire is relatively thin, and the thermal physical properties of aluminum and steel are quite different, which leads to the aluminum coating being easily damaged during the production of the aluminum clad steel wire, and the steel being easily exposed, resulting in decreased corrosion resistance and low bonding strength. In addition, the uneven coating leads to different corrosion resistance of the aluminum clad steel wire, affecting the conductivity and corrosion resistance of the aluminum clad steel wire. The tensile properties of the existing aluminum clad steel wire are difficult to meet the requirements for application in optical cable accessories, and it is necessary to improve the tensile strength of the aluminum clad steel wire.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The forming and coating process of high, medium and low strength aluminum-clad steel wires for optical cable accessories comprises the following steps:

[0008] S1. The modified steel wire is placed in a wire drawing machine for drawing, and then washed and dried to obtain the drawn modified steel wire.

[0009] S2. The aluminum wire is glued onto the surface of the drawn modified steel wire to form strands to obtain a semi-finished aluminum clad steel wire.

[0010] S3. Add the composite gel and carbon fiber into ethanol and stir evenly to obtain a composite filler.

[0011] Among them, carbon fiber is used as a filler and is filled between the semi-finished aluminum-clad steel wires together with the composite gel. During the high-temperature extrusion coating process, the carbon fiber is randomly distributed between the layers of the aluminum-clad copper wire, which improves the density, absorbs external stress, and enhances the mechanical strength of the aluminum-clad copper wire.

[0012] S4. The semi-finished aluminum-clad steel wire is immersed in the composite filler, taken out, dried, placed in a continuous extrusion coating machine for extrusion, and then the wire is taken up after cooling and drying to obtain the initial aluminum-clad steel wire.

[0013] S5. Add the initial aluminum clad steel wire into the composite, stir, take out, and dry to obtain the finished aluminum clad steel wire.

[0014] Furthermore, in step S1, the total compression rate in the wire drawing machine is 95-96%, and the drawing speed is 340-360 m / min; the diameter of the modified steel wire after drawing is 2.7-3 mm.

[0015] Furthermore, in step S2, the diameter of the aluminum wire is 1-1.5 mm, the aluminum content is 96.5-97.1%, the Si and Fe contents are 0.95-1%, and the Cu content is 0.05-0.2%.

[0016] Furthermore, in step S3, the ratio of the composite gel, carbon fiber and ethanol is (2-2.7) g: (0.2-0.5) g: (30-40) mL.

[0017] Furthermore, in step S4, the temperature in the mold cavity of the continuous extrusion coating machine is 450-500° C., the pressure is 60-80 MPa, and the coating speed is 100-200 m / min.

[0018] Furthermore, the dosage ratio of the semi-finished aluminum clad steel wire and the composite filler is (7-9) g: (35-45) mL.

[0019] Furthermore, the initial aluminum-clad steel wire and composite material dosage ratio is (10-14) g: (18-22) mL.

[0020] Furthermore, the modified steel wire is prepared by etching the pretreated steel wire with mixed acid and then reacting the pretreated steel wire with copper salt and tin salt.

[0021] Furthermore, the copper salt is selected from hydrated copper chloride.

[0022] Furthermore, the tin salt is selected from tin chloride pentahydrate and stannous chloride dihydrate.

[0023] Further preferably, the tin salt is selected from tin chloride pentahydrate.

[0024] Further, the modified steel wire is specifically prepared by the following steps:

[0025] A1. Add the pretreated steel wire into the mixed acid, stir and etch for 30 minutes, take it out, wash it with deionized water 3 times, wash it with anhydrous ethanol 3 times, and dry it in a 50°C oven for 10 minutes to obtain the acid-etched pretreated steel wire.

[0026] Among them, the mixed acid formed by urea, hydrogen peroxide and oxalic acid can react with the unremoved oxide on the surface of the pretreated steel wire to remove the oxide layer. After the mixed acid etching, the hydroxide and oxalate in the hydrogen peroxide and oxalic acid combine with the metal ions on the surface of the steel wire, so that the surface of the steel wire carries a large number of oxygen-containing functional groups, which improves the surface wettability and is conducive to the formation of concave-convex nanoparticles on the surface of the pretreated steel wire.

[0027] Furthermore, the dosage ratio of the pretreated steel wire and the mixed acid is (4-6) g:(25-35) mL.

[0028] A2. Add copper salt and tin salt to deionized water, stir evenly, add citric acid and acid-etched pretreated steel wire, stir to obtain dispersion A, add sodium citrate and sodium borohydride to deionized water, stir evenly, add 0.3 mol / L sodium hydroxide aqueous solution to adjust the pH to 12 to obtain solution B, mix solution A and solution B, stir at 300 rpm until a precipitate is formed, collect the precipitate by centrifugation, wash the precipitate three times with a mixture of ethanol and deionized water, and dry it in a -20°C freezer for 24 hours to obtain modified steel wire.

[0029] Among them, citric acid is used as a chelating agent, and the carboxyl group it contains can chelate with the copper ions and tin ions produced by the dissociation of copper salts and tin salts to form a stable complex, which effectively controls the release rate of metal ions. The carboxyl group contained in citric acid can also be combined with the oxygen-containing functional groups on the surface of the acid-etched pretreated steel wire through chemical bonds, so that the complex is deposited on the surface of the acid-etched pretreated steel wire, which helps to form nanoparticles on the surface of the acid-etched pretreated steel wire.

[0030] Furthermore, sodium borohydride is used as a reducing agent and sodium citrate is used as a surfactant. Under alkaline conditions (provided by sodium hydroxide aqueous solution), after co-precipitation reduction treatment, Cu6Sn5 nanoparticles with a size of 2-5 μm are formed on the surface of the acid-etched pretreated steel wire. The nanoparticles are arranged and distributed in sequence on the acid-etched pretreated steel wire to form a concave-convex structure, which increases the surface roughness of the steel wire and improves the interfacial bonding strength between the steel wire core and the aluminum wire, which is conducive to the formation of high-strength aluminum-clad copper wire.

[0031] Furthermore, in dispersion A, the amount ratio of copper salt, tin salt, deionized water, citric acid, and acid-etched pretreated steel wire is (0.3-0.4) g: (0.56-0.6) g: (15-25) mL: (0.1-0.3) g: (1-2) g.

[0032] Furthermore, in solution B, the dosage ratio of sodium citrate, sodium borohydride, deionized water, and sodium hydroxide aqueous solution is (1.6-1.8) g: (0.1-0.2) g: (45-55) mL: (0.1-0.3) mL.

[0033] Furthermore, the specific operation of pre-treating the steel wire is: the steel wire is brushed 2-3 times with a No. 70 steel wire brush, and then tempered to obtain the pre-treated steel wire.

[0034] Among them, the steel wire is brushed with a No. 70 steel wire brush to remove the surface oxide layer to achieve a surface free of oxide scale and other media, and then tempered to effectively reduce the brittleness of the steel wire and eliminate or reduce its internal stress, thereby improving the stability and service life of the steel wire.

[0035] Furthermore, the steel wire is selected from 72B high carbon steel wire with a diameter of 2.1-2.5 mm, a carbon content of 0.71-0.73%, a Si content of 0.1-0.3%, and a Mn content of 0.75-0.77%.

[0036] Furthermore, the tempering temperature is 450-600°C, and the tempering time is 0.5-2h.

[0037] Furthermore, the mixed acid is prepared by the following steps: adding hydrogen peroxide and urea solution with a concentration of 8-12 mol / L into deionized water, stirring, adding oxalic acid solution with a concentration of 20-30 mol / L, stirring evenly, to obtain a mixed acid.

[0038] Furthermore, the dosage ratio of hydrogen peroxide, urea, oxalic acid solution, and deionized water is (1-3) mL: (2-4) mL: (6-8) mL: (7-9) mL.

[0039] Furthermore, the composite gel is prepared by mixing the composite nanoparticles with polyethylene glycol and acrylic acid and stirring the mixture for reaction, and is specifically prepared by the following steps:

[0040] Ammonium persulfate, N,N-methylenebisacrylamide and acrylic acid were added to deionized water, stirred for 30 minutes to obtain a mixed solution, the composite nanoparticles and polyvinyl alcohol were mixed, stirred at 78°C until the polyvinyl alcohol was completely dissolved, added to the mixed solution, stirred and reacted at 70°C for 10 minutes, and cooled to room temperature to obtain a composite gel.

[0041] Among them, ammonium persulfate is used as a catalyst to make N,N-methylenebisacrylamide and acrylic acid copolymerize. The carboxyl and amino groups contained in the formed copolymer can be combined with the hydroxyl groups of polyvinyl alcohol through chemical bonds to produce a cross-linking reaction, and the composite nanoparticles can also be embedded in the cross-linked network structure to form a conductive gel with a cross-linked network structure. It has high toughness and tensile strength, and is filled between the aluminum-clad copper wires to improve the tensile strength and conductivity.

[0042] Furthermore, the dosage ratio of ammonium persulfate, N,N-methylenebisacrylamide, acrylic acid, deionized water, composite nanoparticles, and polyvinyl alcohol is (0.1-0.3) g: (0.3-0.7) g: (8-12) g: (3-7) mL: (0.2-0.4) g: (8-12) g.

[0043] Furthermore, the composite nanoparticles are prepared by surface treating graphene oxide with oxalic acid, mixing with sodium stannate and antimony white, and then reacting with water to obtain

[0044] Furthermore, the graphene oxide has a diameter of 1-2 μm and a thickness of 40-50 μm.

[0045] More preferably, the graphene oxide has a diameter of 1.5 μm and a thickness of 45 μm.

[0046] Furthermore, the hydrothermal reaction temperature is 180-220° C., and the hydrothermal reaction time is 7-9 h.

[0047] Further, the composite nanoparticles are specifically prepared by the following steps:

[0048] B1. Add oxalic acid and graphene oxide to deionized water, stir evenly, add 36% hydrochloric acid by mass, stir and react for 10 minutes, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 10 minutes to obtain pretreated graphene oxide.

[0049] Among them, the carboxyl group contained in oxalic acid can be combined with the hydroxyl group on the surface of graphene oxide through chemical bonds, so that oxalic acid is grafted on the surface of graphene oxide, so that graphene oxide can stably adsorb metal ions, which is conducive to the synthesis of nano antimony tin oxide on the surface of graphene oxide.

[0050] Furthermore, the dosage ratio of oxalic acid, graphene oxide, deionized water, and hydrochloric acid is (2-4) g:(0.3-0.7) g:(45-55) mL:(0.1-0.3) mL.

[0051] B2. Add antimony white to a 0.2 mol / L sodium hydroxide aqueous solution, stir for 5 min to obtain a sodium antimonite solution, add sodium stannate to deionized water, stir, add the sodium antimonite solution, pretreated graphene oxide and 33% sulfuric acid by mass, stir at 60°C for 1 h, place in an autoclave, after hydrothermal treatment, take out the precipitate, wash the precipitate with deionized water 3 times to remove sulfate, then wash with ethanol 3 times, and dry in an oven at 80°C for 10 min to obtain composite nanoparticles.

[0052] Among them, sulfuric acid is used as a precipitant to promote the reaction and co-precipitation of tin ions and antimony ions in sodium antimonite solution and sodium stannate to form tin-antimony precipitates. The surface of the pretreated graphene oxide contains oxalic acid groups, which can also combine with the tin and antimony ions in sodium stannate and antimony white, so that the tin-antimony precipitate is deposited on the surface of the graphene oxide. Further, it is hydrothermally treated at 200°C for 8 hours to cause a dehydration reaction, and the tin-antimony precipitate crystallizes and grows, and antimony is doped into the lattice of tin dioxide to form nano-tin antimony oxide on the surface of the graphene oxide.

[0053] Furthermore, the dosage ratio of antimony white and sodium hydroxide aqueous solution is (0.1-0.3) g: (8-12) mL.

[0054] Furthermore, the dosage ratio of sodium stannate, deionized water, sodium antimonite solution, pretreated graphene oxide, and sulfuric acid is (3-4) g:(18-22) mL:(4-6) mL:(0.3-0.7) g:(0.1-0.3) mL.

[0055] Furthermore, the composite is prepared by mixing the carboxymethyl chitosan thio derivative and the camellia oleifera shell extract, specifically by the following steps:

[0056] The camellia oleifera shell extract is added into ethanol, stirred evenly, and then added into the carboxymethyl chitosan thio derivative, stirred to obtain a composite.

[0057] Among them, the polar groups of the camellia oleifera shell extract interact with the hydroxyl and amino groups rich in carboxymethyl chitosan thio derivatives, and can combine with the aluminum layer on the surface of the aluminum-clad steel wire through hydrogen bonds, so that the complex is coated on the surface of the aluminum-clad steel wire to form an anti-corrosion layer.

[0058] Furthermore, the usage ratio of the camellia oleifera shell extract and the carboxymethyl chitosan thioderivative is (2-3) g:(18-22) mL.

[0059] Furthermore, the camellia oleifera shell extract is specifically prepared by the following steps:

[0060] The camellia oleifera shell was washed with clean water, dried, and ground into powder in a grinder. The camellia oleifera shell powder was immersed in a 40% ethanol solution by mass, stirred for 2 hours, and then condensed and refluxed for 3 hours. The solid impurities were removed by filtration, the liquid was absorbed, and stirred at 85°C until the solvent evaporated to obtain a concentrate. The concentrate was dried in an oven at 60°C for 10 minutes to obtain a camellia oleifera shell extract.

[0061] Furthermore, the dosage ratio of camellia oleifera shell powder and ethanol solution is (8-12) g:(45-55) mL.

[0062] Furthermore, the carboxymethyl chitosan thio derivative is specifically prepared by the following steps:

[0063] Mix acetonitrile, ammonium thiocyanate and octyl chloride, stir at 0°C for 1 hour, collect the filtrate by filtration, add carboxymethyl chitosan to the filtrate, stir for 24 hours, filter out impurities, wash twice with acetonitrile, wash three times with ether, and dry in an oven at 60°C for 10 minutes to obtain the carboxymethyl chitosan thio derivative.

[0064] Among them, acetonitrile is used as a solvent and ammonium thiocyanate is used as a catalyst to cause a substitution reaction between carboxymethyl chitosan and octyl chloride, and an octyl group is introduced into the carboxymethyl chitosan, so that the carboxymethyl chitosan has amphiphilicity, and the hydrophilic group can be combined with the surface of the aluminum-clad steel wire to form an anti-corrosion layer on the surface of the aluminum-clad steel wire.

[0065] Furthermore, the amount ratio of grafted cellulose, modifier and composite filler is (4-5) g: (25-35) mL: (0.3-0.7) g.

[0066] Furthermore, compared with the prior art, the present invention has the following beneficial effects:

[0067] (1) In the technical scheme of the present invention, the pretreated steel wire is etched with mixed acid to react with the unremoved oxide on the surface of the pretreated steel wire, and the surface of the pretreated steel wire carries a large number of oxygen-containing functional groups, which improves the surface wettability and is conducive to the formation of concave-convex nanoparticles on the surface of the pretreated steel wire; Cu6Sn5 nanoparticles with a size of 2-5 μm are formed on the surface of the acid-etched pretreated steel wire, and the Cu6Sn5 nanoparticles are arranged and distributed in sequence on the acid-etched pretreated steel wire to form a concave-convex structure, which increases the surface roughness of the steel wire and improves the interface bonding force between the steel wire core and the aluminum wire. In the high-temperature extrusion process of the aluminum-clad steel wire, the composite filler and the aluminum wire glued on the surface of the steel wire can be embedded in the formed concave-convex structure to increase the bonding strength, thereby improving the density of the aluminum-clad steel wire and the tensile performance, avoiding the large difference in thermal physical properties between aluminum and steel, which leads to the aluminum coating being easily damaged during the aluminum-clad steel wire processing. In addition, the Cu6Sn5 nanoparticles have good electrical and thermal conductivity and do not affect the electrical conductivity of the aluminum-clad steel wire.

[0068] (2) In the technical scheme of the present invention, graphene oxide is surface treated with oxalic acid, so that graphene oxide can stably adsorb metal ions, which is conducive to the synthesis of nano antimony tin oxide on the surface of graphene oxide; nano antimony tin oxide is synthesized on the surface of graphene oxide treated with oxalic acid, and the synthesized nano antimony tin oxide has good electrical conductivity. Graphene oxide provides a good electrical conduction path. The two are compounded and filled between the aluminum-clad copper wires, which have good electrical conductivity. The lamellar structure of graphene oxide has good corrosion resistance, which improves the corrosion resistance of the aluminum-clad copper wire. In addition, nano antimony tin oxide is synthesized on the surface of graphene oxide and filled between the aluminum-clad copper wires. During the high-temperature extrusion process, the nano antimony tin oxide falls off, and its nano size can be filled into the micro gaps of the aluminum-clad copper wires, thereby improving the density and avoiding the gaps in the aluminum-clad copper wires that lead to a decrease in electrical conductivity; the composite nanoparticles, polyethylene glycol and acrylic acid form a conductive gel with a cross-linked network structure, which has high toughness and tensile strength and is filled between the aluminum-clad copper wires to improve the tensile strength and electrical conductivity.

[0069] (3) In the technical solution of the present invention, the composite filler is filled between the semi-finished aluminum clad steel wires. During the high-temperature extrusion process, the carbon fibers and composite gel in the composite filler interact with each other and combine with the concave-convex structure on the surface of the modified steel wire, thereby increasing the bonding strength between the aluminum wire and the copper wire, making the coating more uniform, and the carbon fibers are randomly distributed between the aluminum clad copper wire layers, thereby increasing the density, absorbing external stress, and enhancing the mechanical properties of the aluminum clad copper wire.

[0070] (4) In the technical scheme of the present invention, the camellia oleifera shell extract is rich in tea saponins, water-soluble polysaccharides, tea polyphenols and flavonoids. As a natural preservative, it can improve the anti-corrosion performance of aluminum-clad steel wire. It also contains more polar groups and heterocycles and can be adsorbed on the surface of aluminum-clad steel wire. Carboxymethyl chitosan is a green corrosion inhibitor with good anti-corrosion performance. An octyl group is introduced into the carboxymethyl chitosan to make the carboxymethyl chitosan amphiphilic. Its hydrophilic group can be adsorbed on the surface of the aluminum-clad steel wire together with the polar group of the camellia oleifera shell extract to form an anti-corrosion layer on the surface of the aluminum-clad steel wire, further enhancing the anti-corrosion performance of the aluminum-clad steel wire. It also serves as an insulating layer coated on the surface of the aluminum-clad steel wire to have an insulating effect. DETAILED DESCRIPTION

[0071] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0072] The raw materials used in the embodiments of the present invention are as follows: 72B high carbon steel wire (Taizhou Jinyou Metal Products Co., Ltd.); aluminum wire (Shijiazhuang Zhongli Zinc Industry Co., Ltd.); acetonitrile, octyl chloride, ammonium thiocyanate (analytical grade, Aladdin Reagent Co., Ltd.); carboxymethyl chitosan (molecular weight 240Kda, degree of substitution 90%, Shanghai MacLean Biochemical Technology Co., Ltd.); hydrogen peroxide (concentration 34%, Jinan Haicheng Chemical Co., Ltd.); urea solution (active ingredient 46%, Jiangsu Jiaren Chemical Co., Ltd.); oxalic acid solution (purity 40%, Nanjing Chemical Reagent Co., Ltd.); hydrated cupric chloride, tin chloride pentahydrate, sodium borohydride (Shanghai Aladdin Biochemical Technology Co., Ltd., analytical grade); citric acid (Huiyuan Environmental Protection Technology Co., Ltd., purity 99%); graphene oxide (Shanghai Super Carbon Graphene Co., Ltd., purity 98%); antimony white (AR, Nantong Hongkai New Materials Technology Co., Ltd.); sodium stannate (Shanghai Yunguan Mechanical and Electrical Equipment Co., Ltd., analytical grade); ammonium persulfate (Huiyuan Environmental Protection Technology Co., Ltd., purity 99%); N,N-methylenebisacrylamide (Shanghai Titan Technology Co., Ltd., purity 99%); acrylic acid (Shanghai Titan Technology Co., Ltd.); polyvinyl alcohol (polyethylene glycol 4000, Shanghai Titan Technology Co., Ltd.).

[0073] The steel wire is selected from 72B high carbon steel wire with a diameter of 2.3 mm, a carbon content of 0.72%, a Si content of 0.2%, and a Mn content of 0.76%.

[0074] The diameter of the aluminum wire is 1.4 mm, and its aluminum content is 99.7%, Si and Fe content is 0.15%, and Cu content is 0.08%.

[0075] The mixed acid is specifically prepared by the following steps:

[0076] Add 2 mL of hydrogen peroxide and 3 mL of 8-12 mol / L urea solution to 8 mL of deionized water, stir, then add 7 mL of 20-30 mol / L oxalic acid solution, stir evenly to obtain a mixed acid.

[0077] The camellia oleifera shell extract is specifically prepared by the following steps:

[0078] Wash the camellia oleifera shell with clean water, dry it, and grind it into powder in a grinder. Immerse 10 g of the camellia oleifera shell powder in 50 mL of 40% ethanol solution by mass, stir for 2 h, and then condense and reflux for 3 h. Then, remove solid impurities by filtration, absorb the liquid, and stir at 85°C until the solvent evaporates to obtain a concentrate. The concentrate is dried in an oven at 60°C for 10 min to obtain a camellia oleifera shell extract.

[0079] The carboxymethyl chitosan thio derivative is specifically prepared by the following steps:

[0080] Mix 10 mL of acetonitrile, 4 g of ammonium thiocyanate, and 6.1 g of octyl chloride, stir at 0°C for 1 h, collect the filtrate by filtration, add carboxymethyl chitosan to the filtrate, stir for 24 h, filter out impurities, wash twice with acetonitrile, wash three times with ether, and dry in an oven at 60°C for 10 min to obtain the carboxymethyl chitosan thio derivative.

[0081] Example 1

[0082] The modified steel wire is specifically prepared by the following steps:

[0083] A1. The steel wire is brushed 2-3 times with a No. 70 steel wire brush and then tempered to obtain a pretreated steel wire. The tempering temperature is 520°C and the tempering time is 1 hour.

[0084] A2. Add 5 g of pretreated steel wire into 30 mL of mixed acid, stir and etch for 30 min, take out, wash with deionized water 3 times, wash with anhydrous ethanol 3 times, and dry in an oven at 50°C for 10 min to obtain acid-etched pretreated steel wire.

[0085] A3. Add 0.34g of hydrated copper chloride and 0.58g of tin chloride pentahydrate to 20mL of deionized water, stir evenly, add 0.2g of citric acid and 1.5g of acid-etched pretreated steel wire, stir to obtain dispersion A, add 1.7g of sodium citrate and 0.15g of sodium borohydride to 50mL of deionized water, stir evenly, add 0.3mol / L of sodium hydroxide aqueous solution to adjust the pH to 12 to obtain solution B, mix solution A and solution B, stir at 300rpm until a precipitate is formed, collect the precipitate by centrifugation, wash the precipitate three times with a mixture of 20mL of ethanol and 10mL of deionized water, and dry it in a -20℃ freezer for 24h to obtain modified steel wire.

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 1 is that Cu6Sn5 nanoparticles are not synthesized on the surface of the steel wire pretreated by acid etching, and the remaining steps and raw materials are synchronized with Example 1.

[0088] A1. The steel wire is brushed 2-3 times with a No. 70 steel wire brush and then tempered to obtain a pretreated steel wire. The tempering temperature is 520°C and the tempering time is 1 hour.

[0089] A2. Add 5 g of pretreated steel wire into 30 mL of mixed acid, stir and etch for 30 min, take out, wash with deionized water 3 times, wash with anhydrous ethanol 3 times, and dry in an oven at 50°C for 10 min to obtain modified steel wire.

[0090] Comparative Example 2

[0091] The difference between this comparative example and Example 1 is that the acid-etched pretreated steel wire is replaced by the pretreated steel wire, and the remaining steps and raw materials are the same as Example 1.

[0092] A1. The steel wire is brushed 2-3 times with a No. 70 steel wire brush and then tempered to obtain a pretreated steel wire. The tempering temperature is 520°C and the tempering time is 1 hour.

[0093] A2. Add 0.34g of copper salt cupric chloride and 0.58g of tin salt tin chloride pentahydrate to 20mL of deionized water, stir evenly, add 0.2g of citric acid and 1.5g of pretreated steel wire, stir to obtain dispersion A, add 1.7g of sodium citrate and 0.15g of sodium borohydride to 50mL of deionized water, stir evenly, add 0.3mol / L sodium hydroxide aqueous solution to adjust the pH to 12 to obtain solution B, mix solution A and solution B, stir at 300rpm until a precipitate is formed, collect the precipitate by centrifugation, wash the precipitate three times with a mixture of 20mL of ethanol and 10mL of deionized water, and dry it in a -20℃ freezer for 24h to obtain modified steel wire.

[0094] Example 2

[0095] The composite gel is specifically prepared by the following steps:

[0096] B1. Add 3 g of oxalic acid and 0.5 g of graphene oxide to 50 mL of deionized water, stir evenly, add 0.2 mL of 36% hydrochloric acid, stir and react for 10 min, filter, wash with deionized water 3 times, and dry in an oven at 60 ° C for 10 min to obtain pretreated graphene oxide.

[0097] B2. Add 0.2g of antimony white to 10mL of 0.2mol / L sodium hydroxide aqueous solution, stir for 5min to obtain sodium antimonite solution, add 3.5g of sodium stannate to 20mL of deionized water, stir, add 5mL of sodium antimonite solution, 0.5g of pretreated graphene oxide and 0.2mL of 33% sulfuric acid as a precipitant, stir at 60°C for 1h, place in an autoclave, hydrothermally treat at 200°C for 8h, take out the precipitate, wash the precipitate with deionized water 3 times to remove sulfate, wash it with ethanol 3 times, and dry it in an oven at 80°C for 10min to obtain composite nanoparticles.

[0098] B3. Add 0.2 g of ammonium persulfate, 0.5 g of N,N-methylenebisacrylamide, and 10 g of acrylic acid to 5 mL of deionized water, stir and mix for 30 minutes to obtain a mixed solution, mix 0.3 g of composite nanoparticles and 10 g of polyvinyl alcohol, stir at 78°C until the polyvinyl alcohol is completely dissolved, add the mixed solution, stir and react at 70°C for 10 minutes, and cool to room temperature to obtain a composite gel.

[0099] Comparative Example 3

[0100] The difference between this comparative example and Example 2 is that nano antimony tin oxide is not synthesized on the surface of pretreated graphene oxide, and the remaining steps are synchronized with Example 2.

[0101] B1. Add 3 g of oxalic acid and 0.5 g of graphene oxide to 50 mL of deionized water, stir evenly, add 0.2 mL of 36% hydrochloric acid, stir and react for 10 min, filter, wash with deionized water 3 times, and dry in an oven at 60 ° C for 10 min to obtain pretreated graphene oxide.

[0102] B2. Add 0.2 g of ammonium persulfate, 0.5 g of N,N-methylenebisacrylamide, and 10 g of acrylic acid to 5 mL of deionized water, stir and mix for 30 minutes to obtain a mixed solution, mix 0.3 g of pretreated graphene oxide and 10 g of polyvinyl alcohol, stir at 78°C until the polyvinyl alcohol is completely dissolved, add the mixed solution, stir and react at 70°C for 10 minutes, and cool to room temperature to obtain a composite gel.

[0103] Example 3

[0104] 2.5 g of camellia oleifera shell extract was added to 20 mL of ethanol and stirred evenly, and then added to 30 mL of carboxymethyl chitosan thioderivative and stirred to obtain a composite.

[0105] Example 4

[0106] The forming and coating process of high, medium and low strength aluminum-clad steel wires for optical cable accessories comprises the following steps:

[0107] S1. The modified steel wire is placed in a wire drawing machine for drawing, washed with deionized water for 3 times, and dried in an oven at 70°C for 10 minutes to obtain the drawn modified steel wire, wherein the total compression rate in the wire drawing machine is 95.5%, the drawing speed is 350m / min, and the diameter of the modified steel wire after drawing is 2.8mm.

[0108] S2. Winding and gluing two aluminum wires on the surface of the drawn modified steel wire to form a strand to obtain a semi-finished aluminum clad steel wire, wherein the diameter of the aluminum wire is 1.4 mm.

[0109] S3. Add 2 g of composite gel and 0.2 g of carbon fiber into 30 mL of ethanol and stir evenly to obtain a composite filler.

[0110] S4. Immerse 7g of semi-finished aluminum-clad steel wire into 35mL of composite filler for 25min, take it out, dry it in a 75℃ oven for 10min, extrude it in a continuous extrusion coating machine, and wind it up after cooling and drying to obtain the initial aluminum-clad steel wire. The temperature in the mold cavity of the continuous extrusion coating machine is 480℃, the pressure is 70MPa, and the coating speed is 150m / min.

[0111] S5. Add 10 g of the initial aluminum-clad steel wire into 18 mL of the composite, stir for 1 h, take out the initial aluminum-clad steel wire, and dry it in an oven at 60° C. for 10 min to obtain the finished aluminum-clad steel wire.

[0112] Example 5

[0113] The forming and coating process of high, medium and low strength aluminum-clad steel wires for optical cable accessories comprises the following steps:

[0114] S1. The modified steel wire is placed in a wire drawing machine for drawing, washed with deionized water for 3 times, and dried in an oven at 70°C for 10 minutes to obtain the drawn modified steel wire, wherein the total compression rate in the wire drawing machine is 95.5%, the drawing speed is 350m / min, and the diameter of the modified steel wire after drawing is 2.8mm.

[0115] S2. Winding and gluing two aluminum wires on the surface of the drawn modified steel wire to form a strand to obtain a semi-finished aluminum clad steel wire, wherein the diameter of the aluminum wire is 1.4 mm.

[0116] S3. Add 2.5 g of composite gel and 0.3 g of carbon fiber into 35 mL of ethanol and stir evenly to obtain a composite filler.

[0117] S4. Immerse 10g of semi-finished aluminum-clad steel wire into 40mL of composite filler for 25min, take it out, dry it in a 75℃ oven for 10min, extrude it in a continuous extrusion coating machine, and wind it up after cooling and drying to obtain the initial aluminum-clad steel wire. The temperature in the die cavity of the continuous extrusion coating machine is 480℃, the pressure is 70MPa, and the coating speed is 150m / min.

[0118] S5. Add 12 g of the initial aluminum-clad steel wire into 20 mL of the composite, stir for 1 h, take out the initial aluminum-clad steel wire, and dry it in an oven at 60° C. for 10 min to obtain the finished aluminum-clad steel wire.

[0119] Example 6

[0120] The forming and coating process of high, medium and low strength aluminum-clad steel wires for optical cable accessories comprises the following steps:

[0121] S1. The modified steel wire is placed in a wire drawing machine for drawing, washed with deionized water for 3 times, and dried in an oven at 70°C for 10 minutes to obtain the drawn modified steel wire, wherein the total compression rate in the wire drawing machine is 95.5%, the drawing speed is 350m / min, and the diameter of the modified steel wire after drawing is 2.8mm.

[0122] S2. Winding and gluing two aluminum wires on the surface of the drawn modified steel wire to form a strand to obtain a semi-finished aluminum clad steel wire, wherein the diameter of the aluminum wire is 1.4 mm.

[0123] S3. Add 2.7 g of composite gel and 0.5 g of carbon fiber into 40 mL of ethanol and stir evenly to obtain a composite filler.

[0124] S4. Immerse 7g of semi-finished aluminum-clad steel wire into 45mL of composite filler for 25min, take it out, dry it in a 75℃ oven for 10min, extrude it in a continuous extrusion coating machine, and wind it up after cooling and drying to obtain the initial aluminum-clad steel wire. The temperature in the die cavity of the continuous extrusion coating machine is 480℃, the pressure is 70MPa, and the coating speed is 150m / min.

[0125] S5. Add 14 g of the initial aluminum-clad steel wire to 22 mL of the composite, stir for 1 h, take out the initial aluminum-clad steel wire, and dry it in an oven at 60° C. for 10 min to obtain the finished aluminum-clad steel wire.

[0126] Comparative Example 4

[0127] The difference between this comparative example and Example 5 is that the modified steel wire is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 5.

[0128] Comparative Example 5

[0129] The difference between this comparative example and Example 5 is that the modified steel wire is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 5.

[0130] Comparative Example 6

[0131] The difference between this comparative example and Example 5 is that the composite gel is replaced by the substance prepared in Comparative Example 3, and the remaining steps are synchronized with Example 5.

[0132] Comparative Example 7

[0133] The difference between this comparative example and Example 5 is that the composite is replaced by carboxymethyl chitosan thio derivative, and the remaining steps are synchronized with Example 5.

[0134] The performance of the finished aluminum-clad steel wires prepared in Examples 4-6 and Comparative Examples 4-7 was tested;

[0135] The conductivity of the finished aluminum clad steel wire prepared above was measured using a QJ84 digital DC bridge.

[0136] According to the ASTM E8 / 8M-2013 test standard, the tensile strength and shear strength of the finished aluminum-clad steel wire prepared above were measured using a universal material testing machine. The separation rate of the chuck was set to 30 mm / min. The length of the finished aluminum-clad steel wire prepared above was 250 mm. Tensile strength = maximum load when the aluminum-clad steel wire breaks (N) / cross-sectional area of ​​the aluminum-clad steel wire (mm 2 ); Elongation at break = (length of aluminum clad steel wire after stretching - length of aluminum clad steel wire before stretching) / length of aluminum clad steel wire before stretching.

[0137] The finished aluminum-clad steel wire prepared as above was placed in a 1 mol / L hydrochloric acid solution and a 1 mol / L sodium hydroxide solution. After soaking for 24 hours, the morphology of the finished aluminum-clad steel wire was observed. The test results are shown in Table 1 below.

[0138] Table 1: Test results

[0139]

[0140] It can be seen from the test results in Table 1 that in Comparative Example 4, the modified steel wire prepared by synthesizing Cu6Sn5 nanoparticles on the surface of the acid-etched pretreated steel wire is used to produce aluminum-clad steel wire, and its strength and conductivity are reduced. This may be because the Cu6Sn5 nanoparticles form a concave-convex structure on the surface of the acid-etched pretreated steel wire, and the composite filler and aluminum wire glued on the surface of the steel wire can be embedded in the formed concave-convex structure, thereby increasing the bonding strength and improving the tensile properties, and the Cu6Sn5 nanoparticles have good conductivity; Comparative Example 5 replaces the acid-etched pretreated steel wire with a modified steel wire prepared by pretreated steel wire, and is used to produce aluminum-clad steel wire, and its strength and conductivity are reduced. This may be because the pretreated steel wire is etched with mixed acid, so that the surface of the steel wire carries a large number of oxygen-containing functional groups, which improves the surface wettability and is beneficial to the pretreatment Concavoconvex nanoparticles are formed on the surface of the steel wire; in Comparative Example 6, the composite gel prepared by synthesizing nano-antimony tin oxide on the surface of pretreated graphene oxide is not filled into the semi-finished aluminum-clad steel wire to prepare the finished aluminum-clad steel wire, and its tensile strength and conductivity are reduced. This may be because the nano-antimony tin oxide synthesized on the surface of graphene oxide is filled between the aluminum-clad copper wires. During the high-temperature extrusion process, the nano-antimony tin oxide falls off, and its nano size can be filled into the tiny gaps of the aluminum-clad copper wires, thereby improving the density and avoiding the presence of gaps in the aluminum-clad copper wires, which leads to a decrease in conductivity; in Comparative Example 7, the composite is replaced by a carboxymethyl chitosan thioderivative coated on the initial aluminum-clad steel wire, and its anti-corrosion performance is reduced. This may be because the oil tea shell extract is rich in tea saponins, water-soluble polysaccharides, tea polyphenols and flavonoids, which can be used as a natural preservative to improve the anti-corrosion performance of the aluminum-clad steel wire.

[0141] The data in Table 1 show that the finished aluminum clad steel wires prepared in Examples 4-6 meet the test performance requirements, while the finished aluminum clad steel wires prepared in Comparative Examples 5-8 do not meet the performance requirements, indicating that the finished aluminum clad steel wires prepared in the present invention have good high, medium and low strengths, and the aluminum clad steel wires are evenly coated without pores and have good electrical conductivity.

[0142] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0143] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for forming and coating high, medium and low strength aluminum-clad steel wires for optical cable accessories, characterized in that: The following steps are involved: S1. The modified steel wire is placed in a wire drawing machine for drawing, and then washed and dried to obtain a modified steel wire after drawing; The modified steel wire is prepared by etching the pretreated steel wire with mixed acid and then reacting with copper salt and tin salt; The mixed acid is prepared by the following steps: adding hydrogen peroxide and a urea solution with a concentration of 8-12 mol / L to deionized water, stirring, adding an oxalic acid solution with a concentration of 20-30 mol / L, stirring evenly, to obtain a mixed acid; S2. The aluminum wire is glued into strands on the surface of the modified steel wire after drawing to obtain a semi-finished aluminum-clad steel wire; S3. Add the composite gel and carbon fiber to ethanol and stir evenly to obtain a composite filler; The composite gel is prepared by mixing composite nanoparticles with polyethylene glycol and acrylic acid and stirring the mixture for reaction; The composite nanoparticles are prepared by treating the surface of graphene oxide with oxalic acid, mixing with sodium stannate and antimony white, and then subjecting the mixture to a hydrothermal reaction; S4. The semi-finished aluminum-clad steel wire is impregnated into the composite filler, removed, dried, placed in a continuous extrusion coating machine for extrusion, cooled, dried and then wound to obtain the initial aluminum-clad steel wire; S5. The initial aluminum-clad steel wire is added to the composite, stirred, removed, and dried to obtain a finished aluminum-clad steel wire; The complex is prepared by mixing carboxymethyl chitosan thio derivative and camellia oleifera shell extract; The carboxymethyl chitosan thio derivative is specifically prepared by the following steps: Mix acetonitrile, ammonium thiocyanate and octyl chloride, stir at 0°C for 1 hour, collect the filtrate by filtration, add carboxymethyl chitosan to the filtrate, stir for 24 hours, filter out impurities, wash twice with acetonitrile, wash three times with ether, and dry in an oven at 60°C for 10 minutes to obtain the carboxymethyl chitosan thio derivative.

2. The method for forming and coating high, medium and low strength aluminum-clad steel wires for optical cable accessories according to claim 1, characterized in that: The specific operation of pretreating the steel wire is as follows: the steel wire is brushed 2-3 times with a No. 70 steel wire brush and then tempered to obtain the pretreated steel wire; the steel wire is selected from 72B high carbon steel wire with a diameter of 2.1-2.5 mm, a carbon content of 0.71-0.73%, a Si content of 0.1-0.3%, and a Mn content of 0.75-0.77%; the tempering temperature is 450-600°C, and the tempering time is 0.5-2h.

3. The method for forming and coating high, medium and low strength aluminum-clad steel wires for optical cable accessories according to claim 1, characterized in that: The copper salt is selected from hydrated copper chloride; the tin salt is selected from one of tin chloride pentahydrate and stannous chloride dihydrate.

4. The method for forming and coating high, medium and low strength aluminum-clad steel wires for optical cable accessories according to claim 1, characterized in that: The graphene oxide has a diameter of 1-2 μm and a thickness of 40-50 μm; the hydrothermal reaction temperature is 180-220° C. and the hydrothermal reaction time is 7-9 hours.

5. The method for forming and coating high, medium and low strength aluminum-clad steel wires for optical cable accessories according to claim 1, characterized in that: In step S1, the total compression rate in the wire drawing machine is 95-96%, and the drawing speed is 340-360 m / min; the diameter of the modified steel wire after drawing is 2.7-3 mm.

6. The method for forming and coating high, medium and low strength aluminum-clad steel wires for optical cable accessories according to claim 1, characterized in that: In step S2, the diameter of the aluminum wire is 1-1.5 mm, the aluminum content is 99.6-99.8%, the Si and Fe contents are 0.1-0.2%, and the Cu content is 0.05-0.1%.

7. The method for forming and coating high, medium and low strength aluminum-clad steel wires for optical cable accessories according to claim 1, characterized in that: In step S3, the ratio of the composite gel, carbon fiber and ethanol is (2-2.7) g: (0.2-0.5) g: (30-40) mL.

8. The method for forming and coating high, medium and low strength aluminum-clad steel wires for optical cable accessories according to claim 1, characterized in that: In step S4, the temperature in the mold cavity of the continuous extrusion coating machine is 450-500°C, the pressure is 60-80MPa, and the coating speed is 100-200m / min.

Citation Information

Patent Citations

  • Metal composite wire and preparation method thereof and conductive wire

    CN111834045A

  • Unbonded aluminum-clad steel stranded wire for photovoltaic flexible support

    CN117457269A